The effects of direct sunlight on light shelf performance under tropical sky - Lim, Yaik-Wah (SAGE Publications Ltd, 2015)
As daylight is dynamic, there is no one common solution for all scenarios. Understanding of sky conditions is the fundamental to effective daylighting. It is more critical in tropical climate where the sky is predominantly intermediate with inconsistent presence of direct sunlight (DSL). Thereby, daylighting performances of several light shelf configurations were experimented with physical scaled model under actual tropical sky conditions. External illuminance and indoor work plane illuminance (WPI) levels were measured concurrently in a reference model and a test model for comparisons. Daylight ratio or daylight factor and WPI uniformity ratio were computed for analysis. From the results, different optimum cases were identified for various sky conditions. Light shelves performed the best under intermediate sky with DSL from low angle. The highest improvement in WPI at deep room area and WPI uniformity were 24.87% and 364.96%, respectively. The performances of light shelves under overcast sky were better than light shelf under intermediate sky without DSL. This paper concluded that designing light shelf by responding to changeable sky conditions and DSL is more crucial than considering the façade orientations. Dynamic light shelf was proposed to configure the optimum cases for each tropical sky conditions.